Do solar energy systems have a mid-life crisis? Valorising renewables and ignoring waste in regional towns in Australia's Northern Territory. (June 2021) - Mathur, Deepika; Gregory, Robin; Hogan, Eleanor
Abstract: As the use of solar systems as an alternate source of energy increases, so too does the volume of waste from decommissioned systems. While several options have been suggested as solutions for the end of life of solar systems in terms of their component elements in urban regions, there is little discussion of managing waste arising in regional areas where volumes are often below necessary thresholds. This paper discusses why solar energy systems in Australia's Northern Territory are being removed and how they are disposed of. Results suggest that there are several social and economic reasons for their removal, as it is not just a matter of failure to generate electric power. Since solar energy generation waste is a new problem, there are few or no social mechanisms in place to manage this waste. The results of this study highlight the need for addressing this gap. This paper inquires into, and attempts to formulate an early definition of this newly emergent social problem, conceptualising it as a sociomaterial issue.